TRPM2 channels mediate ROS-induced actin remodeling and cell migration of prostate cancer cells - Pengwei Qi; Jingting Zhao; Hongtian Zhang; Xingyu Liu; Qing You; Jianguo Niu; Xiangming Ye; Fangfang Li (BMC Cancer)
Abstract Background Actin remodeling plays important roles in pathophysiological processes such as cancer metastasis and angiogenesis. Reactive oxygen species (ROS) are signaling molecules thought to regulate cell migration by remodeling actin cytoskeleton. Earlier, we demonstrated that Transient receptor potential melastatin 2 (TRPM2) channels mediates H2O2-induced actin remodeling and cell migration in HeLa cells by manipulating Ca2+ and Zn2+. However, the mechanism by which ROS produced in models more relevant to pathophysiological circumstances affect the actin cytoskeleton, remains poorly unknown. Therefore, this study aimed to explore the effect of ROS produced from pathophysiological conditions on actin cytoskeleton and cell migration. And then investigates the role of TRPM2 channels in the regulation of these types of ROS-induced actin remodeling and cell migration in prostate cancer cells. Methods The study utilized various molecular probes, reagents, and cell culture techniques. Prostate cancer (PC)-3 and DU145 cell line were cultured and treated with different compounds to induce ROS production and actin remodeling. The actin cytoskeleton was stained with phalloidin or labelled with pActin-tdTomato plasmid and imaged using confocal microscopy. Zn2+ and Ca2+ levels were measured by Fluozin3-AM and Fluo4-AM probes respectively. Cell migration as-says were performed to assess the role of TRPM2 channels. Results We demonstrated that both H2O2 and palmitate induces TRPM2-dependent elevation of cytosolic Ca2+ and Zn2+, leading to actin remodeling both in PC-3 and DU145 cells. Inhibition or knockdown of TRPM2 channels or chelation of Zn2+ significantly reduced these effects. Conclusions TRPM2 channels and TRPM2-mediated Zn2+ are essential in ROS-induced actin remodeling and cell migration in prostate cancer cells. Preventing TRPM2 channel activation and chelating Zn2+ may offer potential therapeutic strategies for preventing cancer metastasis. Further research is needed to identify molecular targets of Zn2+ in the actin cytoskeleton and cancer cell migration.